2022
DOI: 10.1038/s44161-022-00060-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor homologous factors serve as a molecular rheostat in tuning arrhythmogenic cardiac late sodium current

Abstract: Voltage-gated sodium (Nav1.5) channels support the genesis and brisk spatial propagation of action potentials in the heart. Disruption of Na V 1.5 inactivation results in a small persistent Na influx known as late Na current ( I Na,L ), which has emerged as a common pathogenic mechanism in both congenital and acquired cardiac arrhythmogenic syndromes. Here, using low-noise multi-channel recordings in heterologous systems, LQTS3 patient-derived iPSCs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
(139 reference statements)
0
11
1
Order By: Relevance
“…Because it was previously shown that FHF2 also plays a crucial role in regulating the late Na + current (I NaL ) (Abrams et al, 2020; Gade et al, 2020; Chakouri et al, 2022), additional voltage-clamp experiments were designed to investigate whether the simultaneous mutation of the nine identified FHF2 phosphorylation sites to alanine, using the FHF2-VY-9A phosphomutant rescue, affects the density of TTX-sensitive I NaL in adult mouse ventricular cardiomyocytes. In accordance with previous studies, these analyses demonstrated that the averaged I NaL density is significantly ( / ?<0.05) increased in FHF2-KD, compared to FHF2-lox, cardiomyocytes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because it was previously shown that FHF2 also plays a crucial role in regulating the late Na + current (I NaL ) (Abrams et al, 2020; Gade et al, 2020; Chakouri et al, 2022), additional voltage-clamp experiments were designed to investigate whether the simultaneous mutation of the nine identified FHF2 phosphorylation sites to alanine, using the FHF2-VY-9A phosphomutant rescue, affects the density of TTX-sensitive I NaL in adult mouse ventricular cardiomyocytes. In accordance with previous studies, these analyses demonstrated that the averaged I NaL density is significantly ( / ?<0.05) increased in FHF2-KD, compared to FHF2-lox, cardiomyocytes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 3, 2023. ; https://doi.org/10.1101/2023.01.31.526475 doi: bioRxiv preprint Regulation of Na V 1.5 by FHF2 phosphorylation 5 cardiac Na V 1.5 channels, tuning both channel availability (Wang et al, 2011a;Park et al, 2016;Wang et al, 2017;Santucci et al, 2022) and I NaL (Abrams et al, 2020;Gade et al, 2020;Chakouri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akin to work on mutant CaMs in LTCC regulation ( 45 ), the reduced affinity of a dominant-negative D96V-CaM mutant for Na V 1.6CTD may not fully explain the impact of this mutation on Na V 1.6 inactivation. Future work will need to examine the cooperativity of additional CaM binding sites and other Na V -interacting proteins, such as FGF homologous factors ( 46 ), with the Na V CTD on Na V inactivation. However, our ITC findings, which point toward the potential proarrhythmic properties of Na V 1.6, especially when dysregulated, provide a useful context for our results implicating the channel in D96V-CaM–mediated arrhythmias.…”
Section: Discussionmentioning
confidence: 99%